Hepatobiliary fascioliasis - Andrade, Daniel Ramos (2017)
Hepatobiliary fascioliasis is a parasitic disease caused by Fasciola hepatica, which is a trematode that primarily infects cattle and sheep, but may also affect humans in endemic areas. There are two phases of the disease: the acute one - where the parasites infect the liver parenchyma; and the subacute / chronic phase - when the parasites reach the biliary ducts and gallbladder, providing typical imaging findings. Because this disease may mimic several hepatobiliary disorders, misdiagnosis or late diagnosis is a concern. Therefore, knowledge of the typical and specific imaging findings is important in accomplishing a correct diagnosis. The authors describe a case of a 49-year-old male that presented with nonspecific liver symptoms. Liver ultrasound, computed tomography and magnetic resonance imaging showed several typical findings of the disease, which helped achieve the diagnosis.